The Mediating Role of Citizen Satisfaction in the Relationship Between Awareness and Continuance Usage of the SANAD App (International Journal of Environmental Sciences, 2025)
Abstract: This study explores the mediating role of citizen satisfaction in the relationship between awareness and continuance usage intention of the SANAD App—Jordan’s official mobile government platform. A quantitative, cross-sectional design was employed using a structured electronic questionnaire administered to 350 Jordanian SANAD App users. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicated a significant positive effect of awareness on satisfaction (β = 0.165, p = 0.003), and of satisfaction on continuance usage intention (β = 0.476, p < 0.001). Furthermore, satisfaction partially mediated the relationship between awareness and usage intention (indirect β = 0.079, p = 0.007). The findings underscore the importance of not only raising awareness but also delivering satisfactory digital experiences to promote sustainable engagement with e-government platforms. This research provides theoretical contributions to digital adoption models and practical guidance for policy makers aiming to enhance user retention in m-government services.